2023
DOI: 10.1097/sla.0000000000005371
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical and Biomechanical Features of Scars Resulting from the Treatment of Burn Contractures Comparing Acellular Dermal Matrices

Abstract: The aim of this study was to compare clinical and biomechanical features of scars resulting from the treatment of burn contractures using different acellular dermal matrices (ADM). Summary Background Data: Extensive burns often lead to severe sequelae, such as skin contractures, that can be treated using ADM to improve the quality of these scars. Methods: A prospective, randomized and controlled clinical trial was performed including patients with burn contractures at least 1-year postburn, treated using split… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…ADM can be divided into allogeneic ADM (humanoid) and heterogeneous ADM (animal‐born) according to material source. The main source of allogeneic ADM is made from donated allogeneic dermis, which retains the extracellular matrix, collagen and proteoglycans in the dermis, 12,13 its biocompatibility is high and the incidence of immune rejection is extremely low; the main source of xenogenic ADM is soft tissue from pigs and cattle, 14 although its structure is similar to that of allogeneic ADM, the inflammatory response after xeno‐ADM transplantation is greater than that of allogeneic ADM due to the large differences in the molecular structure of the histocompatibility complex between donors and receptors and the composition of the basement membrane. Studies have found that scar growth is obvious during the healing process if the wound lacks the dermis layer, and studies have also shown that the lack of elastic fibres and collagen arrangement disorder is the most important histological features of scar tissue 15 .…”
Section: Discussionmentioning
confidence: 99%
“…ADM can be divided into allogeneic ADM (humanoid) and heterogeneous ADM (animal‐born) according to material source. The main source of allogeneic ADM is made from donated allogeneic dermis, which retains the extracellular matrix, collagen and proteoglycans in the dermis, 12,13 its biocompatibility is high and the incidence of immune rejection is extremely low; the main source of xenogenic ADM is soft tissue from pigs and cattle, 14 although its structure is similar to that of allogeneic ADM, the inflammatory response after xeno‐ADM transplantation is greater than that of allogeneic ADM due to the large differences in the molecular structure of the histocompatibility complex between donors and receptors and the composition of the basement membrane. Studies have found that scar growth is obvious during the healing process if the wound lacks the dermis layer, and studies have also shown that the lack of elastic fibres and collagen arrangement disorder is the most important histological features of scar tissue 15 .…”
Section: Discussionmentioning
confidence: 99%
“…These treatments include, among others, burn treatments, hernia repair, breast reconstruction, etc. [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Moreover, there are several reports on the use of ADMs in gynaecological reconstructive surgery [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A longer research period may be planned for our future work. Another limitation of our study was the lack of surgical scar assessment, such as the Vancouver Scar Scale (VSS) and durometer and cutometer evaluation, 44 which would help to support the research conclusions. These scar assessments would certainly be carried out in our future work.…”
Section: Biomaterials Science Papermentioning
confidence: 97%